When is a parasite not a parasite? Effects of larval tick burdens on white-footed mouse survival - Hersh, Michelle H. (2014)
Many animal species can carry considerable burdens of ectoparasites: parasites living on the outside of a host's body. Ectoparasite infestation can decrease host survival, but the magnitude and even direction of survival effects can vary depending on the type of ectoparasite and the nature and duration of the association. When ectoparasites also serve as vectors of pathogens, the effects of ectoparasite infestation on host survival have the potential to alter disease dynamics by regulating host populations and stabilizing transmission. We quantified the impact of larval Ixodes scapularis tick burdens on both within-season and overwinter survival of white-footed mice (Peromyscus leucopus) using a hierarchical Bayesian capture-mark-recapture model. I. scapularis and P. leucopus are, respectively, vectors and competent reservoirs for the causative agents of Lyme disease, anaplasmosis, and babesiosis. Using a data set of 5587 individual mouse capture histories over sixteen years, we found little evidence for any effect of tick burdens on either within-season or overwinter mouse survival probabilities. In male mice, tick burdens were positively correlated with within-season survival probabilities. Mean maximum tick burdens were also positively correlated with population rates of change during the concurrent breeding season. The apparent indifference of mice to high tick burdens may contribute to their effectiveness as reservoir hosts for several human zoonotic pathogens.